The measurement of successful management via a net profit maximization model with ten factors and financial accounting disclosure policy - case of Vinamilk in F&B Industry in Vietnam - Nga Le Thi Viet; Lan Nguyen Thi Ngoc; Yen Ly Lan; Huy Dinh Tran Ngoc; Thuy Do Minh (Zielona Góra: Faculty of Economics and Management Press)
When a firm has better disclosure policy of financial accounting information it will attract more investment. Many factors affecting accounting information disclosure policy include firm size, leverage, industry characteristics, investor types, etc. And good financial accounting data disclosure will help to reduce risk level of firms.
Keywords: successful management; profit maximization; financial accounting data; stock prices; GDP growth; inflationary; risk free rate; arket interest rate; skuteczne zarządzanie; maksymalizacja zysku; dane księgowe; kurs akcji; wzrost PKB; inflacja; stopa procentowa